Valorization Of Waste Transformer Oil As Alternative Carbon Substrate For Polyhydroxyalkanoate Production By Transformer Oil-Degrading Bacteria - Shehu, Idris (2023)
The growing problems of environmental pollution resulting from accumulation of synthetic plastic wastes have been generating great concern. Consequently, a sustained effort is needed to provide better alternatives to the non-biodegradable plastics. However, the production cost of biodegradable, eco-friendly and better substitutes such as polyhydroxyalkanoates remain high. This research aimed to assess the suitability of waste transformer oil as an alternative carbon substrate for polyhydroxyalkanoates production.